Faktor-faktor yang Berhubungan dengan Dukungan Sosial pada Mahasiswa Profesi Ners di masa pandemi COVID-19 - Ailine Yoan Sanger; Ferdy Lainsamputty; Geby Sabatina Yacobus (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
Background: Heavy burden were experienced by professional nursing students such as academic, financial, and psychological problems. Adequate social support is needed, especially during clinical practice in time of the COVID-19 pandemic. Objective: The study aimed to examine the relationship between sociodemographic factors and social support of professional nursing students during the pandemic. Method: The study design was a descriptive correlational and cross-sectional with 102 samples, recruited using purposive sampling technique from a nursing campus in North Sulawesi. The questionnaire used was the Multidimensional Scale of Perceived Social Support (MSPSS). Independent T-Test, One-Way ANOVA, and Pearson correlation were performed to test the relationship between variables. Results: Social support had significant differences with gender, place of residence, relationship status, religion, and knowledge of COVID-19 (p<0.05). Conclusion: Respondents who received higher social support were female students, living outside their own boarding house or home, having spouse, and having good knowledge of COVID-19.